Total Synthesis of Leupyrrins A1 and B1, Highly Potent Antifungal Agents from the Myxobacterium Sorangium cellulosum. Issue 14 (12th January 2017) - Thiede, Sebastian; Wosniok, Paul R.; Herkommer, Daniel; Debnar, Thomas; Tian, Maoqun; Wang, Tongtong; Schrempp, Michael; Menche, Dirk
Abstract: Invited for the cover of this issue is the group of Dirk Menche at the University of Bonn. The image depicts leupyrrins A1 and B1, potent antifungal agents from the myxobacterium Sorangium cellulosum . Read the full text of the article at 10.1002/chem.201604445 . Abstract : " The overall high yields and reliability of the route will enable more detailed biological evaluation of these scarce metabolites ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 3300 ff. (DOI:10.1002/chem.201604445 ).